Вплив відстані між соплами форсунок на характеристики протитечійно-струминного змішувача напоїв - Самойчук, Кирило Олегович; Самойчук, Кирилл Олегович; Samoichuk, Kyryl; Ялпачик, Володимир Федорович; Ялпачик, Владимир Федорович; Yalpachyk, Volodymyr; В'юник, Ольга Володимирівна; Вьюник, Ольга Владимировна; Viunyk, Olha; Полудненко, Ольга Володимирівна; Полудненко, Ольга Владимировна; Poludnenko, Olha (Мелітополь: ТДАТУ, 2019)
UK: У статті наведено результати аналітичних і експериментальних досліджень. Представлена аналітично визначена залежність відстані між соплами форсунок від діаметру сопла за умови отримання найвищої продуктивності змішувача. Представлено загальний вид пристрою для експериментальних досліджень процесу змішування рідин. За результатами аналітичних і експериментальних досліджень побудовано залежності продуктивності змішувача від відстані між соплами форсунок при різних значеннях тиску подачі рідини. RU: в статье приведены результаты аналитических и экспериментальных исследований. Представлена зависимость расстояния между соплами форсунок от диаметра сопла из условия получения наивысшей производителя смесителя, определённая аналитическим методом. Представлен общий вид устройства для экспериментальных исследований процесса смешивания жидкостей. По результатам аналитических и экспериментальных исследований построены зависимости производительности смесителя от расстояния между соплами форсунок при разных значениях давления подачи жидкости. EN: Today, the soft drinks are in great demand. At their manufacture one of the main processes is mixing of the blended syrup or concentrate with prepared water, namely mixing liquids. Therefore, the development and introduction into production of mixers, which will provide high-quality mixing at a minimum consumption of energy and time is relevant. As a result of analysis of different methods of mixing fluids counter-jet mixing was highlighted as the most promising. The article is devoted to the analytical and experimental determination of the dependence on the performance of the mixer from the distance between nozzle's orifice, which is necessary for the creation of an analytical model of counter-jet mixer of liquids. Analytical studies were carried out based on the classical hydrodynamic's dependencies. For conducting experimental research of the process counter-jet mixing were designed and manufactured an experimental device, which is a pair of coaxially installed jet ejectors which provides a collision of fluid jets. In the jet ejectors the liquid and the mixing component are mixing in a certain ratio. As a result of analytical studies, a dependence is obtained that allows to determine the minimum value of the distance between nozzle's orifices, to receive highest mixer performance. The dependencies of the mixer's performance from the distance between for diameters 1-8 mm was constructed. The influence of the distance between nozzle's orifices on the performance of the counterjet mixer is determined experimentally. With increasing distance performance increases. This is because of the pressure that occurs in the area of the collision of the jets decreases, and consequently increases the differential pressure at the inlet and outlet nozzle. An increase in the pressure drop also leads to an increase of the speed of jets at the moment of the collision, which in turn leads to improving the quality of mixing components. The obtained results can be used in constructing an analytical one models of counter-current-jet mixers, homogenizers and others hydraulic machines.
Влияние расстояния между соплами форсунок на характеристики противоточно-струйного смешивания жидкостей
The influence of the distance between nozzle's orifices on the of the characteristics counter-jet mixer
Keywords: змішування; експеримент; рідина; відстань між соплами форсунок; продуктивність